After 10–7: trauma, resilience and satisfaction with life among retired police officers. Issue 2 (28th December 2020) - Parnaby, Patrick; Broll, Ryan
Abstract : Purpose: Most research on trauma, resilience and well-being among police officers focusses on those still on active duty. Comparatively speaking, and despite an aging workforce and established negative health outcomes, similar inquiries involving police retirees are not as common. The purpose of this paper is to examine the effects of on- and off-the-job trauma and resilience on satisfaction with life among a sample of retired police officers. Design/methodology/approach: Data were collected via a cross-sectional nonprobability electronic survey of police retirees in Ontario, Canada. While controlling for employment-related variables and demographic characteristics, a series of hierarchical multiple regression models were used to examine the effects of on- and off-the-job trauma and resilience on satisfaction with life among a sample of 932 participants. Findings: The analysis indicates that off-the-job trauma and both personal and social dimensions of resilience contribute uniquely to satisfaction with life among police retirees. Moreover, this full model explains nearly 37% of the variance in satisfaction with life. Originality/value: This study's findings offer further direction to those working to support the health and well-being of officers currently on the job and those well into their retirement years.